C1q/TNF-related protein-1: Potential biomarker for early diagnosis of autism spectrum disorder. (10th February 2022) - Raeisy, Hamed; Bayati, Paria; Noorbakhsh, Farshid; Hakim Shooshtari, Mitra; Eftekhar Ardebili, Mehrdad; Shekarabi, Mehdi; Mojtabavi, Nazanin
Introduction: Autism spectrum disorders (ASDs) are neurodevelopmental diseases characterized by communication inabilities, social interaction impairment, repetitive behavior, as well as learning problems. Although the exact mechanism underlying this disease is still obscure, researchers believe that several factors play a significant role in its development and pathogenesis. Some authors have reported an association between adipokines family and autism. C1q/TNF-related protein-1 (CTRP1) is a member of the adipokines family, and we hypothesized that this adipokine might have an influential role in the pathogenesis of ASDs. Since there is no specific marker for screening the disease, we evaluated CTRP1 as a potential marker for achieving this purpose. Methods: Blood samples were collected from 82 (41 ASDs boys, 41 healthy boys as controls) children aged 5–7 years old. CTRP1 gene expression and CTRP1 serum level were measured by quantitative realtime-PCR and enzyme-linked immunosorbent assay methods, respectively. Results: It was found that CTRP1 is significantly elevated in autistic children in comparison to healthy controls, both at the gene expression level, as well as at the serum level; demonstrating a good diagnostic value with a good range of sensitivity and specificity for detecting ASDs. Conclusion: CTRP1 expression is elevated in ASDs boys aged 5–7 years old, suggesting a role for this adipokine in ASDs pathophysiology. Also, receiver operating characteristic curve analyses revealed that this adipokine could be utilized as a diagnostic biomarker for differentiating ASDs patients from healthy individuals along with other recently proposed biomarkers.